Who feels unwelcome in your biochemistry programme?. (8th June 2020) - Burgstahler, Sheryl
Abstract : Has the design of your biochemistry courses and facilities unintentionally excluded certain students and faculty? We live in an era of heightened awareness about nondiscrimination with respect to underrepresented groups defined by gender, race, ethnicity, socioeconomic status and other characteristics. Have you considered issues related to the inclusion of talented students and faculty who have disabilities? If not, today is a good day to start doing so. This article shares an approach for proactively designing post-secondary courses, materials, services and facilities that are welcoming and accessible to this minority group along with others, while reducing the need for additional accommodations for individuals with disabilities.